2021
DOI: 10.5194/cp-17-2451-2021
|View full text |Cite
|
Sign up to set email alerts
|

Early Holocene cold snaps and their expression in the moraine record of the eastern European Alps

Abstract: Abstract. Glaciers preserve climate variations in their geological and geomorphological records, which makes them prime candidates for climate reconstructions. Investigating the glacier–climate system over the past millennia is particularly relevant first because the amplitude and frequency of natural climate variability during the Holocene provides the climatic context against which modern, human-induced climate change must be assessed. Second, the transition from the last glacial to the current interglacial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 128 publications
(166 reference statements)
7
14
0
Order By: Relevance
“…The ice margin geomorphology another level below denoted as J5 (Figure 4d), differs from J6 in the absence of a distinct ridge and in the abundance of boulders of which two were selected for dating and yield ages of 11.6 ± 0.2 ka and 11.8 ± 0.2 ka. Two boulders in the main valley embedded in lateral and in terminal moraines (J3-4, Figure 3c-d) give ages of 10.4 ± 0.2 ka and 11.6 ± 0.2 ka and extend the Holocene moraine chronology published for the valley by Braumann, et al 9 .…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…The ice margin geomorphology another level below denoted as J5 (Figure 4d), differs from J6 in the absence of a distinct ridge and in the abundance of boulders of which two were selected for dating and yield ages of 11.6 ± 0.2 ka and 11.8 ± 0.2 ka. Two boulders in the main valley embedded in lateral and in terminal moraines (J3-4, Figure 3c-d) give ages of 10.4 ± 0.2 ka and 11.6 ± 0.2 ka and extend the Holocene moraine chronology published for the valley by Braumann, et al 9 .…”
Section: Resultssupporting
confidence: 81%
“…For the period between ca. 12 and 10 ka, moraine chronologies from different places in the Alps, including data presented in this study, have shown that ice retreat and therefore warming was not linear, but was interrupted by centennial-scale cooling [8][9][10][11] . For the (pre-)Bølling period, it is still unclear whether ice retreat was steady and of such magnitude that most glaciers in the European Alps retreated to the highest cirques or disappeared altogether 7 .…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations